Depression Severity and Depression Stigma Among Students: A Survey of Universities in Five Countries. Issue 11 (November 2020) - Musa, Arif; Ashraf, Jahanzeb; Tsai, Feng-Jen; Abolmagd, Samir; Liu, Ciny; Hussain, Hajra; Voslarova, Eva; Khalil, Mohamed A.; Wolitzky-Taylor, Kate B.; Lee, Danny; Sugar, Jeffrey; Pendi, Kasim; et al.
Abstract : Abstract: In the university setting, mental disorders have come under greater scrutiny and more attention has been given toward addressing the social stigmas associated with mental illness in an effort to promote mental well-being and improve mental health care delivery on-campus. Depression has been previously linked to a reduction in quality of life, suicidal ideation, and poor academic performance. However, few studies have directly compared the burden of depression or stigmatized views between multiple universities. As a result, this cross-sectional study of university students from five countries was performed to determine the burden of depressive disorders, the stigmatizations of beliefs related to depression, and international variation. A questionnaire consisting of a sociodemographic survey, Patient Health Questionnaire-9 (PHQ-9), and Depression Stigma Scale (DSS) was distributed via multiple routes to undergraduate and graduate students at institutions in the United States, Taiwan, United Arab Emirates, Egypt, and Czech Republic. The point prevalence of depression was determined by using the algorithm scoring method of the PHQ-9. Depression severity was determined according to the summed-item scoring method of the PHQ-9. The degree of stigmatization of beliefs was determined by continuous scores on the DSS subscales for personal and perceived stigma. Differences in depression severity, personal stigma, and perceived stigma were determined according to analysis of variance and further studied using post hoc Tukey's tests. Responses were collected from students in the United States ( n = 593), United Arab Emirates ( n = 134), Taiwan ( n = 217), Egypt ( n = 105), and Czech Republic ( n = 238). Of 1287 responses, 30.7% ( n = 396) screened positive for a depressive disorder: 18.0% ( n = 232) for major depressive disorder and 12.7% ( n = 164) for another depressive disorder. Depression severity differed internationally ( p < 0.001). Emirati students significantly exhibited most depression followed by Czech, American, and Taiwanese students (all p s < 0.001). There was also a difference between students of different countries in terms of personal stigma ( p < 0.001), with Emirati students holding more stigmatized personal views than Czech, American, Egyptian, and Taiwanese students (all p s < 0.001). Students similarly demonstrated differences in terms of personal stigma ( p < 0.001). Egyptian students exhibited the most perceived stigma followed by Emirati, Taiwanese, American, and Czech students (all p s < 0.001). These findings suggest a high point prevalence of depression among university students and differences in the severity of depression, which has implications for the delivery of mental health care in this population. There were significant differences in terms of personal and perceived stigma between university students, indicating resource allocation for university-based campaigns to reduce depression stigma may need to be tailored to the population. After implementation of stigma reduction programs, future follow-up surveys can be done to compare degrees of stigma before and after the intervention.